2020
DOI: 10.1111/ppc.12572
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived loneliness and depression in the elderly and influencing factors

Abstract: Purpose: This study was carried out to determine the relationship between perceived loneliness and depression in the elderly and influencing factors Design and Methods: This cross-sectional descriptive study was conducted with 501 elderly. Data were collected with the questionnaire form, the elderly loneliness scale and the geriatric depression scale. Findings: A positive relationship was found between depression and loneliness. Loneliness, applying to a family health center/hospitalization, educational level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The present study determined that loneliness and depression predicted each other across time, which is consistent with the findings of previous studies (Hsueh et al., 2019; Fernandes et al., 2018; Holvast et al., 2015). Although both loneliness and depression are linked to negative emotions, large number studies have defined loneliness and depression as two independent variables (Isik et al., 2020; Shaw & Gant, 2002). For example, loneliness is caused by negative thoughts and feelings of being isolated and disconnected from others, which tend to stem from problems in interpersonal relationships (Russell et al., 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The present study determined that loneliness and depression predicted each other across time, which is consistent with the findings of previous studies (Hsueh et al., 2019; Fernandes et al., 2018; Holvast et al., 2015). Although both loneliness and depression are linked to negative emotions, large number studies have defined loneliness and depression as two independent variables (Isik et al., 2020; Shaw & Gant, 2002). For example, loneliness is caused by negative thoughts and feelings of being isolated and disconnected from others, which tend to stem from problems in interpersonal relationships (Russell et al., 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness can be related to life satisfaction, including thoughts about lack of support. 20 Studies have shown that loneliness is related to depression, lower quality of life, [21][22][23][24] and greater vulnerability to physical and mental health problems in older individuals. [24][25][26] A Finnish study found strong evidence that social isolation has an adverse effect on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, loneliness alone is an independent risk factor for mortality in old age [ 2 , 11 , 12 ]. Loneliness is also closely related to poor quality of life and mental health [ 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%